2021
DOI: 10.1007/s12034-021-02472-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the absorption of 1-chloro-1,2,2,2-tetrafluoroethane on carbon nanotubes: an ab initio study

Abstract: Enhancing the absorption of 1-chloro-1,2,2,2-tetrafluoroethane on carbon nanotubes an ab initio study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Quantum theory of atoms in molecule is a paramount quantum mechanics tool used for analyzing the type of chemical interaction and strength of the interaction occurring between two bonded atoms. , QTAIM provides adequate information on the type of inter- and intramolecular interactions such as covalent (shared) interaction and noncovalent (closed shell) interactions, e.g., electrostatic interaction, van der Waals interaction, and hydrogen bond interaction that is evident between two bonded atoms . Also, QTAIM depends fully on the electron density or charge distribution present in the chemical bond interaction in the sense that a decrease in in the electron density corresponds to a closed-shell interaction, while an increase in electron density is in relation to a covalent (shared) interaction .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum theory of atoms in molecule is a paramount quantum mechanics tool used for analyzing the type of chemical interaction and strength of the interaction occurring between two bonded atoms. , QTAIM provides adequate information on the type of inter- and intramolecular interactions such as covalent (shared) interaction and noncovalent (closed shell) interactions, e.g., electrostatic interaction, van der Waals interaction, and hydrogen bond interaction that is evident between two bonded atoms . Also, QTAIM depends fully on the electron density or charge distribution present in the chemical bond interaction in the sense that a decrease in in the electron density corresponds to a closed-shell interaction, while an increase in electron density is in relation to a covalent (shared) interaction .…”
Section: Resultsmentioning
confidence: 99%
“…Global reactivity descriptors were estimated based on Koopmans approximation using the following equations 32 34 where η, S , χ, and ω are chemical hardness, softness, electrophilicity, and nucleophilicity, respectively. Adsorption energies of the studied gases adsorbed on the respective nanocages were also computed using eq 8 ( 35 , 36 ) E cage/gas is the total energies of the gas-adsorbed nanocage and E gas and E cage are the total energy of the adsorbed gas and isolated nanocage, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It was also shown that, laplacian electron density for NU/POM(NO 2 ) systems had the lowest value that was the only negative recorded (À 0.0650) and with the highest electronic energy density (À 0.1284) which indicate the occurrence of shared interaction, thus implies the covalent nature of the chemical bonds for both molecules that has been studied. [32][33][34][35] In addition, Yar et al [36] said the laplacian of the electron density with energy density are in the range of H-bonding.…”
Section: Quantum Theory Of Atoms In Molecules Descriptionmentioning
confidence: 99%
“…Eight pesticides, two industrial chemicals, and two unanticipated industrial byproducts, together known as "the dirty twelve," are utilized in home items including insecticides, solvents, and even medications, as well as in industry and agriculture. [6][7] Furthermore, the brominated flame-retardants and polycyclic aromatic hydrocarbons are among the "nasty nine" (BFRs). [8] Because of its harmful, bio-accumulative and persistent environmental characteristics, chloronaphthalenes, the majority of which are semi-volatile, were added to the list of prohibited POPs during the seventh meeting of the Conference of the Parties to the Stockholm Convention in May 2015.…”
Section: Introductionmentioning
confidence: 99%